Competitive Advantage of Malaysian Small Medium Enterprises: Impact of Supply Chain management Practices, environmental Uncertainty and Supply Chain Flexibility - Lian, Chew Li (2018)
Today’s businesses are compelled to develop flexible capabilities to enable it to effectively respond to greater volatility and complexity of the fast changing environments. The current study proposes that a firm that adopts supply chain management practices would achieve competitive advantage and this is because of the influence of flexibility in the supply chain which in turn is driven by environmental uncertainties. The research framework consists of four constructs namely environmental uncertainty, supply chain management practice, supply chain flexibility and competitive advantage. The relationship between these constructs shall be investigated within the same framework in the context of SMEs in Malaysia, thus, filling the gap in supply chain literature in Malaysia by providing a new framework for research. The data collection method used is a self-administered survey questionnaire and the instruments of measures had been adopted from previous researches. Data collected from the pilot study was used to conduct exploratory factor analysis to assess the dimensionality of items in view of the new research environment and business condition. Subsequently, a field study using an online self-administered survey questionnaire yielded 250 usable responses from the SME industry. Structural equation modelling was used to analyze the data results as it produces better results in terms of fitness and more accurate and efficient in estimating multiple items of the latent constructs. iii The results support the hypothesized relationships presented in the theoretical framework, that is, the independent path which examine the effect of the exogenous constructs and endogenous constructs as well as the mediating path which examine the role of supply chain flexibility as the mediator in the relationship of supply chain management practices and competitive advantage. Some of the gaps in literature that this study was able to fill include expanding on existing models by integrating the four constructs in one theoretical framework and tested the theory in the SME sector. Testing mediation using the triangle approach in this study is novel because it has not been seen to be used for empirical supply chain management studies locally before. One of the most important contribution of this study is employing the resampling method of bootstrapping to test the mediation effect of supply chain flexibility, thus managed to achieve full mediation which had not been demonstrated in previous studies before.